Concurrent Disorders and Health Care Utilization Among Homeless and Vulnerably Housed Persons in Canada. Issue 1 (2nd January 2018) - Zhang, Linda; Norena, Monica; Gadermann, Anne; Hubley, Anita; Russell, Lara; Aubry, Tim; To, Matthew J.; Farrell, Susan; Hwang, Stephen; Palepu, Anita
ABSTRACT: Objective: Individuals who are homeless or vulnerably housed have a higher prevalence of concurrent disorders, defined as having a mental health diagnosis and problematic substance use, compared to the general housed population. The study objective was to investigate the effect of having concurrent disorders on health care utilization among homeless or vulnerably housed individuals, using longitudinal data from the Health and Housing in Transition Study.Methods: In 2009, 1190 homeless or vulnerably housed adults were recruited in Ottawa, Toronto, and Vancouver, Canada. Participants completed baseline interviews and four annual follow-up interviews, providing data on sociodemographics, housing history, mental health diagnoses, problematic drug use with the Drug Abuse Screening Test (DAST-10), problematic alcohol use with the Alcohol Use Disorders Identification Test (AUDIT), chronic health conditions, and utilization of the following health care services: emergency department (ED), hospitalization, and primary care. Concurrent disorders were defined as the participant having ever received a mental health diagnosis at baseline and having problematic substance use (i.e., DAST-10 ≥ 6 and/or AUDIT ≥ 20) at any time during the study period. Three generalized mixed effects logistic regression models were used to examine the independent association of having concurrent disorders and reporting ED use, hospitalization, or primary care visits in the past 12 months.Results: Among our sample of adults who were homeless or vulnerably housed, 22.6% ( n = 261) reported having concurrent disorders at baseline. Individuals with concurrent disorders had significantly higher odds of ED use (adjusted odds ratio [ AOR ] = 1.71; 95% confidence interval [CI], 1.4–2.11), hospitalization ( AOR = 1.45; 95% CI, 1.16–1.81), and primary care visits ( AOR = 1.34; 95% CI, 1.05–1.71) in the past 12 months over the four-year follow-up period, after adjusting for potential confounders.Conclusions: Concurrent disorders were associated with higher rates of health care utilization when compared to those without concurrent disorders among homeless and vulnerably housed individuals. Comprehensive programs that integrate mental health and addiction services with primary care as well as community-based outreach may better address the unmet health care needs of individuals living with concurrent disorders who are vulnerable to poor health outcomes.